2018
DOI: 10.1111/ans.14723
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐operative carcinoembryonic antigen predicts survival following colorectal cancer surgery with curative intent

Abstract: We identified pre-operative CEA as an independent predictor of OS and DFS on an individual level. CEA offers additional prognostic value to TNM staging and should be requested routinely as part of the pre-operative work-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Jung et al analyzed 472 CRC patients and found that preoperative CEA was an independent prognostic factor with regard to CSS and DFS, and CA 19-9 also had prognostic value for CSS and DFS20. Another study that enrolled 237 patients found that CEA predicted OS (HR 2.50, 95% CI 1.17-5.36, P = 0.02) and DFS (HR 1.78, 95% CI 1.02-3.13, P = 0.04)7. Similar to our study, Gao et al analyzed the relationship between serum tumor markers (including CEA, CA19-9, CA72-4 and CA125) and clinicopathologic factors and suggested that the combination of multiple preoperative tumor markers could improve the early diagnosis and treatment of CRC21.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Jung et al analyzed 472 CRC patients and found that preoperative CEA was an independent prognostic factor with regard to CSS and DFS, and CA 19-9 also had prognostic value for CSS and DFS20. Another study that enrolled 237 patients found that CEA predicted OS (HR 2.50, 95% CI 1.17-5.36, P = 0.02) and DFS (HR 1.78, 95% CI 1.02-3.13, P = 0.04)7. Similar to our study, Gao et al analyzed the relationship between serum tumor markers (including CEA, CA19-9, CA72-4 and CA125) and clinicopathologic factors and suggested that the combination of multiple preoperative tumor markers could improve the early diagnosis and treatment of CRC21.…”
Section: Discussionmentioning
confidence: 96%
“…CEA is an acid glycoprotein involved in cell recognition and cell adhesion and is secreted by solid tumors. The level of preoperative CEA influences the prognosis of multiple tumors, such as gastric cancer, lung cancer and CRC5, 6, 7. Furthermore, CEA levels are correlated with the metastasis and recurrence of CRC after curative surgery8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, carcinoembryonic antigen (CEA) is a circulation glycoprotein that has been widely associated with colon cancer for over half a century 6–10 . Normally produced by the gastrointestinal tract during foetal development, in the adult life it is mostly expressed within epithelial cells of colon and rectum and its circulating levels are increased in 27–70% of CRC patients 6–8,11,12 . In 2000, the Colorectal Working Group of the American Joint Committee on Cancer (AJCC) suggested adding initial CEA levels in the conventional TNM classification of CRC (the ‘C‐stage’), but its inclusion has yet to take place 7,11,13 .…”
Section: Introductionmentioning
confidence: 99%
“…CEA has been established as an attractive prognostic variable for colorectal cancer. Previous studies have shown that elevated preoperative CEA levels represent an independent risk factor (3)(4)(5)(18)(19)(20). Additionally, failure to normalize CEA levels after resection has been shown to play an important role in poor prognosis (21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Carcinoembryonic antigen (CEA) is an effective serum biomarker that is recommended as part of the preoperative work-up and postoperative follow-up routine in patients with colorectal cancer. Multiple studies have demonstrated the usefulness of preoperative CEA for predicting the prognosis of colon cancer patients (3)(4)(5), while other studies have suggested that postoperative CEA performed better than preoperative CEA in prognostic stratification; moreover, the recurrence-free survival of patients with an elevated preoperative CEA level but a normalized postoperative CEA level was not significantly different from that of patients with a normal preoperative CEA (6). In the present study, we aimed to determine whether preoperative or postoperative serum CEA could be used to optimize the current prognostic model in patients with stage III colon cancer.…”
Section: Introductionmentioning
confidence: 99%